Visual navigation around curved obstacles - Blake, A; Brady, M; Cipolla, R; Xie, Z; Zisserman, A (IEEE, 1991)
An approach to path-planning around smooth obstacles that exploits visually derived geometry is proposed. A moving robot can scan the silhouette or apparent contour of an obstacle and estimate a minimum length path. This is done by seeking geodesics which can be extrapolated smoothly, around the obstacle and towards the goal. Preliminary implementation of this idea uses a real-time visual contour tracker running at 16 Hz, with a camera mounted on an Adept robot arm. The camera first dithers to generate visual motion, a safe path is estimated, and the robot steers the camera around the obstacle with a clearance of a few millimeters.